Nine years of dental assistance from an intellectual disability patient: clinical case report - Cançado-Figueiredo, Márcia (2021)
Intellectual disability is a neuropsychiatric disorder that affects cognitive, motor, social and language functions. The difficulty of patients and their caregivers in performing oral hygiene is linked to the failure to preserve their health. The objective of this article is to report the dental care of a 55-year-old patient diagnosed with intellectual disability caused by perinatal anoxia. All the necessary dental procedures were carried out, always preserving the pertinent care for the patient's care, providing her with a positive emotional benefit, through constant stimulation, gradual inclusion of the patient and her caregiver in the dental environment, associated with the preventive-educational reinforcement activities. It is concluded that the knowledge of the particularities of the patient reported with intellectual disability was extremely important for the conduct of her dental treatment, being possible to have adequate behaviors in her oral rehabilitation.